The Relationship of Knowledge and Personal Hygiene with Duration of Perineum Wound Healing in Postpartum Mothers in Basuki Rahmad Community Health Center in Bengkulu City - Metha Fahriani; Aisyah Purnama Putri; S. Effendi (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
In Bengkulu Province in 2017, the absolute number of maternal deaths was 28, consisting of 6 maternal deaths, 10 maternal deaths, 12 postpartum maternal deaths. This research aimed to study the association between mother’s knowledge and personal hygiene with duration of perineal wound healing in postpartum mothers in the Basuki Rahmad Community Health Center in Bengkulu City. The type of this research was Analytical Survey with cross sectional design. The population in this study were all post partum mothers who gave birth as many as 32 mothers. The sampling technique used was Total Sampling. The data collection in this study used primary data through questionnaires. Data analysis of this research uses univariate and bibvariat analysis with Chi-Square test (χ2) and Contingency Coefficient test (C). The results found : of the 32 mothers, there were 21 mothers who had long duration of wound healing, 17 mothers had insufficient knowledge, 20 mothers had poor personal hygiene. There was a relationship between mother’s knowledge with the duration of perineal wound healing in puerperal mothers, with the category of close relationship, and there was a relationship of personal hygiene with the duration of perineal wound healing in puerperal mothers, with a close relationship category. It is expected that the community health center can increase mother’s knowledge about recovery of perineal wounds and personal hygiene by giving counseling to pregnant women during Antenatal Care and Pregnant Mothers Class visit. Keywords: knowledge, personal hygiene, wound healing